Little-Known Metalwork in Trecento Venice and the Veneto - Mezzacasa, Manlio Leo (ASPICE HUNC OPUS MIRUM: Festschrift on the occasion of Nikola Jakšić’s 70th birthday, 2020)
This essay discusses two little known pieces of sacred goldsmith's art: a chalice preserved in the parish church of San Simon in Vallada Agordina, in the northern Veneto, and a chalice from the church of San Samuele in Venice, now held in Santo Stefano. The former can be placed in the context of a large series of liturgical vessels produced in Venice and the Venetian area around the second quarter of the fourteenth century. The latter is a rare example of non-Venetian, possibly Central Italian goldsmithery still preserved in Venice, and can be dated to the second half of the Trecento.